Response of forest soil euglyphid testate amoebae (Rhizaria: Cercozoa) to pig cadavers assessed by high-throughput sequencing - Seppey, Christophe; Fournier, Bertrand; Szelecz, Ildikò; Singer, David; Mitchell, Edward; Lara, Enrique (My University, 2016)
Decomposing cadavers modify the soil environment, but the effect on soil organisms and especially on soil protists is still poorly documented. We conducted a 35-month experiment in a deciduous forest where soil samples were taken under pig cadavers, control plots and fake pigs (bags of similar volume as the pigs). We extracted total soil DNA, amplified the SSU ribosomal RNA (rRNA) gene V9 region and sequenced it by Illumina technology and analysed the data for euglyphid testate amoebae (Rhizaria: Euglyphida), a common group of protozoa known to respond to micro- environmental changes. We found 51 euglyphid operational taxonomic units (OTUs), 45 of which did not match any known sequence. Most OTUs decreased in abundance underneath cadavers between days 0 and 309, but some responded positively after a time lag. We sequenced the full-length SSU rRNA gene of two common OTUs that responded positively to cadavers; a phylogenetic analysis showed that they did not belong to any known euglyphid family. This study confirmed the existence of an unknown diversity of euglyphids and that they react to cadavers. Results suggest that metabarcoding of soil euglyphids could be used as a forensic tool to estimate the post-mortem interval (PMI) particularly for long-term (>2 months) PMI, for which no reliable tool exists.
Keywords: Environmental DNA; Euglyphid testate amoebae; Illumina high-throughput sequencing; Metabarcoding; SSU rRNA gene V9 region; Forensic ecology